Diffusion-weighted magnetic resonance imaging in non-invasive monitoring of antiangiogenic therapy in experimental tumor model - Kharuzhyk, S.A.; Petrovskaya, N.A.; Vosmitel, M.A. (Experimental Oncology, 2010)
Aim: To show usefulness of diffusion-weighted magnetic resonance imaging (MRI) for non-invasive assessment of experimental tumor after antiangiogenic treatment. Methods: M1 sarcoma was implanted to the peritoneal cavity of the rat and allowed to grow to a palpable tumor size. Animal was treated with a single injection of endothelial growth factor antibody Bevacizumab (Avastin). Serial MRI scanning including diffusion-weighted sequence was performed before and up to 100 h after treatment. Animal was sacrificed thereafter and MRI data were correlated with morphology. Results: Apparent diffusion coefficient (ADC) maps derived tumor necrotic area correlated well with histology-derived tumor necrotic area. ADC threshold of 1.39 × 10–3 mm2/s appeared to be optimal for tumor necrosis quantification in this tumor model and allowed to follow temporal changes of tumor internal structure after treatment. Conclusion: Diffusion-weighted MRI permits non-invasive tissue characterization without the need for exogenous contrast agents and, therefore, may be used to individualise therapy and to monitor tumor response.